2020
DOI: 10.1038/s41598-020-69439-4
|View full text |Cite
|
Sign up to set email alerts
|

Prevalence and causes of vision impairment and blindness in the Russian ural eye and medical study

Abstract: To assess prevalence of mild vision impairment (MVI; best corrected visual acuity (BCVA) < 6/12 to 6/18 in the better eye), moderate-to-severe vision impairment (MSVI; BCVA < 6/18 but ≥ 3/60) and blindness (BCVA < 3/60) in a local population in Russia, we conducted the population-based Ural Eye and Medical Study. Out of 7,328 eligible individuals aged 40 + years, 5,899 (80.5%) individuals participated. MVI was present in 184 (3.1%; 95% confidence interval (CI) 2.7, 3.6) individuals, MSVI in 182 (3.1%; 95% CI 2… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

4
15
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 10 publications
(20 citation statements)
references
References 26 publications
4
15
1
Order By: Relevance
“…In the UEMS population, which included participants with substantially younger ages, myopic maculopathy was the second most common factor associated with irreversible blindness (2 of 8 individuals [25.0%] with irreversible blindness, or 2 of 5893 individuals [0.03%] in the total study population) and the second most common factor associated with irreversible moderate to severe VI (11 of 73 individuals [15.1%] with irreversible moderate to severe VI, or 11 of 5893 individuals [0.2%] in the total study population). 23 The prevalence of myopic maculopathy as a factor associated with blindness (0.3% in our study vs 0.03% in the UEMS) and moderate to severe VI (1.1% in our study vs 0.2% in the UEMS) was thus higher in our older population compared with the younger population of the UEMS. Even if one assumes a further age-related increase in the prevalence of myopic maculopathy, the 5- to 10-fold higher prevalence of myopic maculopathy as a factor associated with blindness or moderate to severe VI in our older study population compared with the middle-aged population of the UEMS suggests that, in the UEMS and UVOS study regions, the prevalence of myopic maculopathy as a factor associated with moderate to severe VI or blindness (in the middle-aged population) may not have substantially increased compared with previous periods.…”
Section: Discussioncontrasting
confidence: 42%
See 3 more Smart Citations
“…In the UEMS population, which included participants with substantially younger ages, myopic maculopathy was the second most common factor associated with irreversible blindness (2 of 8 individuals [25.0%] with irreversible blindness, or 2 of 5893 individuals [0.03%] in the total study population) and the second most common factor associated with irreversible moderate to severe VI (11 of 73 individuals [15.1%] with irreversible moderate to severe VI, or 11 of 5893 individuals [0.2%] in the total study population). 23 The prevalence of myopic maculopathy as a factor associated with blindness (0.3% in our study vs 0.03% in the UEMS) and moderate to severe VI (1.1% in our study vs 0.2% in the UEMS) was thus higher in our older population compared with the younger population of the UEMS. Even if one assumes a further age-related increase in the prevalence of myopic maculopathy, the 5- to 10-fold higher prevalence of myopic maculopathy as a factor associated with blindness or moderate to severe VI in our older study population compared with the middle-aged population of the UEMS suggests that, in the UEMS and UVOS study regions, the prevalence of myopic maculopathy as a factor associated with moderate to severe VI or blindness (in the middle-aged population) may not have substantially increased compared with previous periods.…”
Section: Discussioncontrasting
confidence: 42%
“…Factors associated with moderate to severe VI and blindness were older age, lower MMSE score, lower dynamometric hand grip force, lower prothrombin index, lower prevalence of previous cataract surgery, and more substantial cylindrical refractive error ( Table 3 ). Although the associations with older age have also been reported in previous studies, 4 , 23 , 25 , 26 , 27 , 28 , 29 the association between a higher prevalence of moderate to severe VI and blindness and lower cognitive function (as measured by MMSE score) is of interest because another study 31 found an association between the prevalence of Alzheimer disease and hearing loss. This finding suggests that cataract surgery (and the provision of best-correcting glasses), in particular, may be a means of reducing the risk of cognitive dysfunction.…”
Section: Discussionmentioning
confidence: 77%
See 2 more Smart Citations
“…Age-related macular degeneration (AMD) is the most common cause of irreversible vision impairment in industrialized countries 1 , 2 . The introduction of anti-vascular endothelial growth factor (anti-VEGF) intravitreal treatment has provided a significant improvement in visual and anatomical prognosis in patients with neovascular AMD (nAMD), and has resulted in significant reduction of AMD-related irreversible vision loss in developed countries 3 .…”
Section: Introductionmentioning
confidence: 99%